Low supply voltage, low quiescent current, ULDO linear regulator - Bontempo, G.; Signorelli, T.; Pulvirenti, F. (2001 8th International Conference on Electronics, Circuits and Systems, 2001)
In this paper a new monolithic Ultra Low Drop-Out (ULDO) linear regulator developed in BCD (Bipolar CMOS, DMOS) technology, 5th generation, is described. It is able to deliver an output current up to 5 A with 150 mV drop-out voltage on the series element at a supply voltage down to 2 V The new regulator has been designed to reduce the quiescent and stand-by currents without degradation of the load transients performance and to guarantee an output voltage high accuracy, better than 1%, thanks to a new trimming structure. 200 /spl mu/A quiescent current and a very low stand-by current, up to 2 /spl mu/A, make the devices suitable for microprocessor applications such as Pentium, cellular phones, automotive and in all applications where power management and stand-by features are needed.